Analisis Faktor Minat Kunjungan Wisata Terhadap Strategi Pengembangan Pariwisata Pantai Mutiara Indah Di Desa Tanjung Limau Kecamatan Muara Badak - Haeruddin, Haeruddin; Sabtohadi, Joko; Luthman, Awang Yacoub (FAKULTAS EKONOMI DAN BISNIS UNIKARTA, 2018)
Abstract:The purpose of this research is to determine the significant effect of attraction on the interest of visit Mutiara Indah Beach in Tanjung Limau Village Muara Badak and to know the significant influence of the facility on the interest of visit Mutiara Indah Beach in Tanjung Limau Village Muara Badak. Based on the analysis and discussion of data on respondents' appraisal of factors comprising attractiveness, facilities, infrastructure, transportation, and comfort to the interest of tourist visit at Mutiara Indah beach at Tanjung Limau Village Muara Badak subdistrict can be concluded that variable of attraction, facility , infrastructure and transportation significantly influence the interest of tourist visitÂ Keywords: Factor Analysis, The Interest of Visit, Tourism Development Strategy